(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze the consumption of antibiotics in the treatment of community-acquired pneumonia (CAP) at the Department of Pediatrics, Quang Nam Central General Hospital in 2023. Subject and method: A quantitative analysis based on the number of days of antibiotic use (DOT) and the length of antibiotic treatment (LOT) through a retrospective review of medical records of pediatric in-patients at the Department of Pediatrics during January 1st to December 31st, 2023 with diagnosis of pneumonia and excluding cases of hospital-acquired pneumonia Results: A total of 416 medical records were included in this study. The average number of days of antibiotic use was 115.9 DOT/100 patient-days. The length of antibiotic treatment was almost equal to the length of hospitalization (88.0 LOT/100 patient-days). The frequently used regimens for initial empirical therapy were combination antibiotic therapy, with DOT/LOT ratios ranging from 1.1 to 1.6. The three groups of antibiotics with the highest consumption were C3G, penicillin/β-lactamase inhibitors, and aminoglycosides, of which, ceftriaxone was the most consumed antibiotic (29.8%). Conclusion: The consumption of antibiotics in the treatment of CAP in the Department of Pediatrics was relatively high, the duration of antibiotic use was long and preferred combination regimens. Further in-depth analysis of problems related to antibiotic use in the treatment of pediatric CAP is needed, thereby implementing interventions to improve the quality of antibiotic use in hospitals.